The euro area at the crossroads. First joint analysis of the macro group - Österreichisches Institut für Wirtschaftsforschung, Vienna (Düsseldorf, 2011)
"The German economy entered the year 2011 buoyantly. The upswing is expected to continue throughout 2011 with GDP increasing at an average rate of 2.7%. Both internal and external demand will drive the economy. In the course of the forecast horizon, however, economic activity will become less vigorous. There are two key reasons for this slowdown: Firstly, the fiscal stimulus packages are coming to an end and fiscal policy is embarking on a restrictive course. Secondly, but more importantly, the sovereign debt crisis in the euro area is unresolved and taking its toll. The crisis countries are experiencing deep economic recessions, not least because of the fiscal austerity measures they had to adopt. The other member states are also turning to fiscal consolidation. This will dampen economic activity in the euro area, the main market for German export goods. The institutes therefore expect lower export growth and weaker investment demand in Germany for next year. All in all, German GDP growth will amount to 1.7% in 2012. The unemployment rate will decline to 6.6 % in 2012 from 7.1% in 2011. Consumer prices will increase by 2 % and 1.5% in 2011 ands 2012, respectively.